Identities Concerning Symmetric f-Biderivations on Lattice (Contemporary Mathematics, 2025)
Recently, the concept of lattice derivation has been reintroduced in the examination of a variety of issues. The intention of the current research is to examine the structure of symmetric f-biderivation on lattices and to provide a description of some related properties. Furthermore, symmetric f-derivations are used to characterize the distributive and modular lattices in the domain of f-biderivations and explore the features of kernel.
Keywords: lattice; distributive (joinitive) lattice; symmetric f-biderivation; monotone